Evaluation of an environmental education program for the prevention of marine litter in sports port - Martín-Jaime, Juan Jesús; Tójar-Hurtado, Juan Carlos; Velasco-Martínez, Leticia Concepción; Estrada-Vidal, Ligia Isabel (My University, 2022)
The design of educational itinearies is a powerful tool in environmental education for the evaluation of urban sustanibability. Studentes and participantas of te programme can obbserve,analyse, reflect an desgina routes tinking about third parties, but at the same time, studentes are being trained in a participatory way in environmental education. The general objective of the programme is for university studentes to learn how to desgin educational itineraries to evaluate urban sustainability. Numerous data were obtained from the application of the programme.
Keywords: Educación ambiental; Contaminación marina; Estudiantes universitarios; Educación - Investigación; Enseñanza - Innovaciones; Puertos; Basuras marinas; Buenas prácticas